Candidate rhizobacteria as plant growth-promoters and root-knot nematode controllers in tomato plants - Chávez-Arteaga, Karen Tatiana (2022)
Meloidogyne incognita root-knot nematode is one of the main causes of tomato root damage and consequently crop production losses. Thus, in in vitro conditions, the number of nematodes hatched eggs (%) at 4 and 6 days and nematode mortality (J2 stage) at 8, 18, and 24 h, were evaluated in Petri dishes containing the candidate rhizobacteria Enterobacter asburiae (BA4-19 and PM3-14), Acinetobacter calcoaceticus (BM2-12), Klebsiella variicola (BO3-4) and Serratia marcescens (PM3-8). The well-known Pseudomonas protegens (CHA0) and P. veronii (R4) were used as controls. In greenhouse conditions, plant height, root weight, and symptoms, as well as gall and nematode numbers, were determined in tomato plants infected by M. incognita and treated with the seven rhizobacteria. In addition, all variables were correlated using Pearson's analysis. In general, a significant correlation was observed among the variables of both experiments, showing the antagonistic capacity of the strains against nematode. It seems, that PM3-8 and PM3-14 strains reduce hatching, and cause mortality of nematodes J2 if compared with CHA0 and R4 strains. Likewise, tomato treated with BM2-12 strain shows a higher height and root weight, as well as a smaller number of galls and nematodes in their roots. This study provides evidence that PM3-8 and PM3-14 strains reduce the M. incognita egg hatching, and that the BM2-12 strain can be a plant growth-promoter potential of tomato plants.